Processing method of honeysuckle flower cigarette tea - KANG HAIBIN (2021)
A honeysuckle flower cigarette tea provided by the invention breaks through the forms of traditional cigarettes and tea leaves, can be used as cigarettes and tea leaves, has taste similar to that of the traditional cigarettes by outer% or above when being used for smoking, is easy to accept, does not contain carcinogens or toxins such as tar and nicotine in combustion products, is smooth in taste,does not choke the nose, and can reduce lung phlegm accumulation; the fragrance can refresh and restore consciousness and relieve fatigue; meanwhile, theophylline contained in the cigarette tea is approximately the same as nicotine in the tobacco in efficacy, so that the dependence of a smoker on the tobacco can be reduced to a certain extent, and the tobacco is replaced; and the honeysuckle flower cigarette tea can be directly brewed as tea, has the aromatic smell of honeysuckle flowers, has the effects of diminishing inflammation, clearing away heat and toxic materials, and Chinese wolfberry is helpful for improvin